2019
DOI: 10.1111/dom.13909
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of empagliflozin as add‐on to insulin in Japanese patients with type 2 diabetes: A randomized, double‐blind, placebo‐controlled trial

Abstract: Aim To assess the efficacy and safety of empagliflozin as add‐on to insulin in Japanese patients with type 2 diabetes (T2D). Materials and methods This multicentre, double‐blind, parallel‐group study randomized Japanese patients with T2D insufficiently controlled with insulin (1:1:1) to empagliflozin 10 mg (n=89), empagliflozin 25 mg (n=90) or placebo (n=90) for 52 weeks. The primary endpoint was change from baseline in glycated haemoglobin (HbA1c) at 16 weeks. Results At 16 weeks, empagliflozin 10 mg and 25 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
5
18
0
1
Order By: Relevance
“…These findings are in line with those of another study that found that 12-week treatment with EMPA monotherapy resulted in similar reductions in HbA1c, FPG, and body weight compared to a placebo in drug-free patients with T2DM [ 40 ]. Reductions in HbA1c, FPG, and body weight were also consistent with those reported from 12-week studies on other SGLT2 inhibitors [ 33 , 41 , 42 ]. EMPA as an added therapy to insulin resulted in a significant reduction in insulin units, consistent with the results reported by [ 43 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings are in line with those of another study that found that 12-week treatment with EMPA monotherapy resulted in similar reductions in HbA1c, FPG, and body weight compared to a placebo in drug-free patients with T2DM [ 40 ]. Reductions in HbA1c, FPG, and body weight were also consistent with those reported from 12-week studies on other SGLT2 inhibitors [ 33 , 41 , 42 ]. EMPA as an added therapy to insulin resulted in a significant reduction in insulin units, consistent with the results reported by [ 43 ].…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have reported the safety and efficacy of EMPA for T2DM [ 11 , 33 , 34 , 35 ]. EMPA was the first in class to not only demonstrate safe SGLT2 inhibition but also cardio- and reno-protective effects in an adequately powered cardiovascular outcome trial [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of randomized clinical trials using empagliflozin are summarized in Table 5. Several trials [12][13][14][15][16][17][18][19][20][21][22][23][24] have shown significant reductions of HbA1c and BW with empagliflozin. Increasing the empagliflozin dose from 10 to 25 mg consistently caused a further reduction in HbA1c (13/16 trials, see Table 5).…”
Section: Discussionmentioning
confidence: 99%
“… References 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 …”
Section: Supporting Informationunclassified